Impact of core muscle strengthening on knee pain, patient outcomes, physical function, and cartilage thickness in knee osteoarthritis: Protocol for a randomized controlled trial - Dias Tina Thomas; Charu Eapen; Atmananda S. Hegde; Prajwal Prabhudev Mane; Saurabh P. Mehta (MethodsX, 2024)
Knee Osteoarthritis (KOA) is a degenerative condition that significantly impacts individuals, causing disability. Routine rehabilitation methods primarily involve knee and hip strengthening exercises. While there is limited evidence supporting the potential benefits of core muscle strengthening in KOA rehabilitation, further research is needed to examine the effects of a structured core muscle strengthening protocol on pain, functional abilities, quality of life, and knee cartilage health. This double-blind, randomized controlled trial seeks to investigate the impact of integrating core muscle strengthening into routine rehabilitation. The study will randomly assign 80 participants to either routine rehabilitation or experimental groups, with both groups receiving routine rehabilitation combined with core strengthening exercises in the experimental group over a twelve-week period. The outcomes measured will include pain levels, patient-reported outcomes, physical functional abilities, core muscle and leg muscle strength, and cartilage height of the femur and tibia. Follow-up assessments will occur in the 4th, 8th, and 12th weeks. This novel study aims to provide valuable insights into the role of core strengthening in KOA rehabilitation, potentially influencing rehabilitation approaches and managing disease progression. • Incorporating core muscle strengthening into routine rehabilitation for KOA could open new possibilities for KOA management. • This study employs outcome measures recommended by OARSI for a thorough evaluation. • Additionally, it will investigate the impact on cartilage health, offering fresh insights into disease progression and the effects of exercise